Is public debt boosting economic growth in SADC? - Sogoni, Zanele (Research of GSB, 2018)
The World Bank estimates that Africa's inadequate infrastructure decreases productivity by around 40 per cent every year and reduces national economic growth by 2 per cent annually. Such disadvantages hinder private sector investment, which is a key driver of job and wealth creation. Financing the development of infrastructure in an appropriate manner has been a leading topic in the continents development agenda. In order to remedy the infrastructure deficit problem, more and more African countries are increasing their public debts by borrowing in the international markets to finance their infrastructure deficits in the hope that it will ultimately spur economic growth and attract more investment. SSA's access to the international markets has grown significantly, facilitated by easing global financial conditions. By end March 2014, 13 countries had issued international sovereign bonds, for reasons that include infrastructure building. The sub-Saharan Africa's region's access to international markets has come under much attention lately as debt levels are rising with fears that they may reach the unsustainable pre –HIPC levels. For example, Zambia's total debt burden stood at an unsustainably high USD5.4 billion in 2005 – equivalent to 74% of the country's GDP and almost 208% of its foreign exchange earnings (IHS Global Insights, 2014). The attainment of debt relief under the IMF and World Bank's Multilateral Debt Relief Initiative (MDRI) in early 2006 dramatically decreased the country's debt holdings to less than 25% of GDP. However, in the third quarter of 2012, the government issued its first Eurobond and raised debt capital of USD 750 million. This was followed by a USD 1 billion Eurobond issue in the second quarter of 2014 (IHS Global Insights, 2014) with the stated intention of using the funds for infrastructural development and maintenance. However, according to the latest IMF statement on Zambia released on 6 June 2014, Zambia's macroeconomic situation, though potentially promising, is in trouble and needs urgent fixing. It appears that the government of Zambia wants an IMF funding arrangement, possibly a bailout (Zambian Economist, 2014). In the face of mounting evidence that access to the international capital markets and rising public debt are more likely to have enhanced vulnerability than growth, this paper examines the determinants of economic growth in a panel of 15 countries. It examines the impact of external debt, total public debt and infrastructure expenditure on economic growth in the southern African region over a period of 10 years (between 2004 and 2014). The findings suggest an inverse relationship between external debt and total public debt against economic growth. The findings also suggest that there is a positive relationship between infrastructure development and economic growth amongst the countries in the southern Africa region. These relationships were found to be insignificant, suggesting that other factors outside of the variables of infrastructure expenditure, external debt and total public debt are influencing economic growth (or slowdown) in the region. The paper also examines the current debt situation in the 15 countries and policy considerations are also presented.